Experimental study on chloride transport of blast-furnace slag blended concrete with crystalline admixture under seawater wet dry cycle - Peng He; Lingwei Liu; Jianying Yu (Case Studies in Construction Materials)
Crystalline admixture could significantly enhance the self-healing ability of cement-based materials. However, when applied to marine engineering, the impact of crystalline admixture on chloride transport in concrete under the combined action of seawater ions and wet dry cycles is not clear yet. Therefore, this paper mainly investigated the influence of crystalline admixture-ion chelator (CA) on the chloride transport behavior of concrete under the action of seawater dry wet cycles. Moreover, the correlation between pore structure and chloride ion diffusion coefficient of concrete was analyzed. Results showed that during the seawater dry wet cycle process, CA had a significant reducing effect on free and total chloride content of 100 % OPC and 50 % blast-furnace slag (BFS) concrete. Moreover, CA could improve chloride binding ability of 100 % OPC and 50 % BFS concrete, reduce the chloride diffusion coefficient. Moreover, CA could enhance the corrosion resistance of 100 % OPC and 50 % BFS concrete, and improve the microstructure. However, the 50 % BFS concrete with CA could only observe small pores and no obvious cracks. The correlation analysis of pore structure parameters and chloride diffusion coefficient of concrete found that compared with gel pores and transition pores, the gross pores, macropores and total porosity of concrete had better correlation with chloride diffusion coefficient. It could be concluded that CA reduced the concrete capillary pores, macropores and total porosity and damage of seawater dry wet cycle to concrete matrix, thus effectively inhibiting the chloride diffusion.